Pharmacognostical Study of Ochrocarpus longifolius Benth and Hook - A Substitute of Mesua ferrea - Ghosh, Kuntal (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Ochrocarpus longifolius Benth and Hook is commonly known as Surapunnaga, Surangi, Lal Nagakeshar. Proper description about Surapunnaga is not available in Brihatrayee.The description of the plant as a substitute of Mesua ferrea is first time available in Nighantu Adarsha under Nagapuspadi varga. The properties (Rasa, Guna, Virya, Vipaka) of Surapunnaga are almost same as Nagakeshara and for this reason Ochrocarpus longifolius is used in various Ayurvedic preparatory medicines like Sunthikhanda and etc. The authentification & macroscopic study of the flower buds of Surapunnaga were done in the department of Pharmacognosy, I.P.G.T.& R.A., Gujarat Ayurveda University of Pharmacy, Jamnagar, Gujarat, India. Flowers have a very pleasant smell, which lasts even when the flowers dry up. Ochrocarpus longifolius exhibits antibacterial, antihelminthic, anti-inflammatory, anti-spasmodic & hypotensive activity.Key words: Ochrocarpus longifolius, Mesua ferrea, Surapunnaga, Surangi, Lal Nagakeshar, Nagakeshar.